Association of patellar bone marrow lesions with knee pain, patellar cartilage defect and patellar cartilage volume loss in older adults: a cohort study. Issue 8 (August 2015) - Wang, J.; Antony, B.; Zhu, Z.; Han, W.; Pan, F.; Wang, X.; Jin, X.; Liu, Z.; Cicuttini, F.; Jones, G.; Ding, C.
Summary: Aim: To examine the cross-sectional and longitudinal associations of patellar bone marrow lesion (BMLs) with knee pain, cartilage defects and cartilage volume in older adults. Methods: A total of 904 randomly selected subjects (mean 62.4 years, 49.9% female) were studied. Fat suppressed T1-weighted spoiled gradient recall and T2-weighted fast spin echo magnetic resonance imaging (MRI) sequences were used to assess cartilage volume, cartilage defects and/or BMLs at baseline ( n = 904) and 2.6 (range: 1.4–4.8) years' follow-up ( n = 414). Knee pain was assessed by self-administered Western Ontario McMaster Osteoarthritis Index (WOMAC) questionnaire at baseline ( n = 904) and follow-up ( n = 790). Results: The prevalence of any patellar BMLs was 19% and was higher in those with tibiofemoral BMLs. In multivariable analyses, patellar BMLs were positively associated with any knee pain at baseline and an increase in knee pain when going up/down stairs (odds ratio (OR): 1.67, 95% confidence interval (CI): 1.08, 2.59) but not with other knee pain subscales. Patella BMLs were also associated with patellar cartilage defects both at baseline and change over time (OR: 1.76, 95% CI: 1.00, 3.70) but not tibiofemoral defects. Patellar BMLs were negatively associated with baseline and change in patella cartilage volume (β: −2.10%, 95% CI: −3.39%, −0.80%). These associations remained significant after further adjustment for tibiofemoral BMLs. Conclusions: Patellar BMLs were consistently associated with increased knee pain especially going up/down stairs, increased patellar cartilage defects, and decreased patellar cartilage volume cross-sectionally and longitudinally, suggesting a predominantly compartment specific role for patellar BMLs.